The eco-design handbook : a complete sourcebook for the home and office. - Fuad-Luke, Alastair, ....- (London : Thames and Hudson, 2002)
1.Objects for living 2.Objects for working 3.Materials 4.Resources
Keywords: Milieubewuste productontwikkeling; Producten